Numerical and experimental study on the combustion pressurization and gaseous products of propellant in a combustor - Chenzhuo Hao; Xing Lv; Zhibin Sun; Jiangong Zhao; Wen Ao (Results in Engineering, 2025)
Propellant combustion in a combustor offers a promising method for environmentally sound disposal but is limited by insufficient theoretical and experimental research. This study investigates how burning surface geometry affects dynamic pressure and gaseous product distribution within a combustor. A validated numerical model was developed and compared with experimental data, examining the impact of burning surface area on peak pressure and gaseous product distribution. Solid propellants with varying surface areas and masses were tested in a sealed combustor using precision pressure sensors and gas chromatography. Results showed a sigmoidal pressure profile, with pressure rise rates nonlinearly dependent on propellant mass and surface area. Major combustion products identified were H₂, CO, CO₂, and HCl. Simulations revealed that reducing the burning surface angle first increased and then decreased H₂, CO, and HCl concentrations and pressure, while smaller individual surface sizes led to consistent increases in both. These findings clarify the relationship between propellant geometry and combustion dynamics. The developed AP/HTPB aluminized propellant model effectively captures pressure variation patterns, supporting its use in controlled combustion for waste propellant disposal.